Ill. bij gedicht "De natuurlijke historie van de Christelijke regeeringsmeerderheid" door L.M. Hermans. . V.l.n.r.: Abraham Kuyper, ? - Hahn, Albert
Ill. bij gedicht "De natuurlijke historie van de Christelijke regeeringsmeerderheid" door L.M. Hermans. V.l.n.r.: Abraham Kuyper, ?.